Analysis of the Feasibility of a Vaccination Campaign against Influenza Epidemic and COVID-19 Pandemic in French Emergency Departments: A National Survey - Ghazali, Daniel Aiham (Vaccines (Basel), 2021)
Background: Vaccination is one of the most effective ways to fight the influenza epidemic and the coronavirus disease 2019 (COVID-19) pandemic, which represent a major public issue. The objective was to investigate the adherence of heads of French emergency departments (ED) and nursing departments on a potential vaccination campaign of healthcare workers (HCW) and patients in ED. Method: In February 2021, ED and nursing department heads were asked to answer a national survey. It included 24 questions designed to cover some dimensions, including characteristics of the hospital and emergency departments (ED) and questions on vaccination. Results: 414 responses out of 800 questionnaires (51.8%) were collected. Scores out of 10 were, respectively, 7 (6–8) and 8 (6–9) for vaccination against influenza and COVID-19 for HCW and 2 (2–3) and 2 (2–4) for ED patients (H = 989.3; p < 0.0001). Multivariate logistic regression found that the existence of a vaccine program in the hospital and the use of point of care influenza PCR in ED were positively associated with the acceptance of influenza vaccination campaign for HCW (p = 0.003) and patients (p = 0.015). Factors limiting adherence to a vaccination program of HCW and patients were lack of medical staff (p = 0.041 for HCW and p < 0.0001 for patients), overcrowded ED (p < 0.001), and the inability to follow up with patients after the ED visit (p < 0.0001). Conclusions: There have been many missed opportunities for influenza vaccination, and there is pressure to vaccinate against COVID-19 as soon as possible. Vaccination campaigns in ED could help to improve vaccination coverage. ED staff are more likely to vaccinate HCW than patients. There are factors that support the implementation of such programs, which can be grouped into a culture of diagnosis, control, and prevention of viral infectious diseases within the hospital and ED. On the other hand, there are limiting factors, such as overcrowding and lack of personnel.